Outcomes of the Evidence-Based Pitocin Administration Checklist at a Tertiary-Level Hospital. (September 2014) - Wojnar, Danuta M.; Cowgill, Karen; Hoffman, Lindsay; Carlson, Hannah
Pitocin, a synthetic form of the hormone oxytocin, is a high-alert medication that heightens patient harm when used incorrectly. This investigation examined the outcomes of an evidence-based Pitocin administration checklist used for labor augmentation at a tertiary-level hospital. Data came from patient records. Using the Perinatal Trigger Tool, N = 372 clinical records ( n = 194 prior to and n = 178 following checklist implementation) were reviewed. Checklist implementation resulted in statistically significant reductions in the duration of hospitalization (1.72 vs. 2.02 days, p = .0005), presence of meconium (23.7% vs. 6.7%, p < .001), maternal fevers (7.2% vs. 2.3%, p = .030), and episiotomies (8.8% vs. 1.7%, p = .002), and clinically important reduction in APGAR scores < 7 at 5 min (3.6%-0.6%, p = .069) and instrumented deliveries (11.9%-8.4%, p = .307). A universal Pitocin checklist implementation can improve birth outcomes and costs of care.